Time Series Transcriptomic Analysis by RNA Sequencing Reveals a Key Role of PI3K in Sepsis-Induced Myocardial Injury in Mice - Yan, Xiao; Zhang, Yun-Long; Han, Xiao; Li, Pang-Bo; Guo, Shu-Bin; Li, Hui-Hua (Frontiers in Physiology, 2022)
Septic cardiomyopathy is the main complication and cause of death of severe sepsis with limited therapeutic strategy. However, the molecular mechanism of sepsis-induced cardiac injury remains unclear. The present study was designed to investigate differentially expressed genes (DEGs) involved in the pathogenesis of septic cardiomyopathy induced by cecal ligation and puncture (CLP) in mice. Male C57BL/6J mice (8-10 weeks old) were subjected to CLP with 21-gauge needles for 24, 48, and 72 hours. Myocardial function was assessed by echocardiography. The pathological changes of the heart were evaluated by hematoxylin and eosin as well as immunohistochemical staining. Time series RNA sequencing was utilized to investigate the gene expression profiles. CLP surgery resulted in a significant decrease of animal survival rate and left ventricle contractile function, and an increase in cardiac dilation and infiltration of proinflammatory cells including Mac-2+ macrophages in a time-dependent manner. RNA sequencing identified 5,607 DEGs in septic myocardium at 24, 48, and 72 hours after CLP operation. Moreover, gene ontology analysis revealed that these DEGs are mainly associated with the biological processes, including cell adhesion, immune system process, inflammatory response, and positive regulation of cell migration. KEGG pathway enrichment analysis indicated that staphylococcus aureus infection, osteoclast differentiation, leishmaniasis, and ECM-receptor interaction were significantly altered in septic hearts. Notably, Pik3r1 and Pik3r5 were localized in the center of the gene co-expression network, and were markedly upregulated in CLP-induced septic myocardium. Further, blocking PI3Kγ by the specific inhibitor CZC24832 significantly protected against sepsis-induced cardiac impairment. The present study uncovers the gene expression signatures of CLP-induced myocardial injury and sheds light on the role of Pik3r5 in septic cardiomyopathy.